PEMBUATAN DESAIN TABUNG BIOGAS 3D MELALUI PROGRAM KULIAH KERJA NYATA TEMATIK (KKNT) - Imam Solikin; Muhammad Sadam; Rahmat Hidayatullah Adly; Eci Meiliana; Muhammad Firly Syahputra; Sela Yulia Sari; Ajeng Septia Dewi; Berry Agustian (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Thematic real work lectures (KKN-T) are one of the community service programs that are included in courses at the Bina Darma University College. The KKN-T program teaches students to be able to participate directly and play an active role in the community, and can seek knowledge and learn experiences that are not obtained in lectures. The KKN-T program carried out by students in Durian Gadis Village is guided by a Field Supervisor. The role of students and lecturers in this KKN-T program is to explore the potential that exists in Durian Gadis Village. one of the potentials developed through this program is the 3D design of biogas tubes for processing cow dung waste.